(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The scientific publication presents the two-year results of research on the study of growth characteristics and the formation of productivity elements of spring rapeseed hybrids depending on the influence of mineral fertilizers and the bioregulator "Fitomare" on gray podzolized soils of Vinnytsia. Field germination of seeds largely depends on varietal characteristics, growing conditions and fertilization options. That is, the highest rates of field seed germination in the years of research using different fertilizer options were obtained from the Belinda hybrid, since this hybrid is characterized by increased resistance to adverse factors in the early stages of vegetation. The best weather conditions at the initial stages of vegetation during the years of research in all presented hybrids were noted in 2020, as they are characterized by smaller changes in temperature regimes compared to 2021. It should also be noted that the use of mineral fertilizers increases the field germination of seeds. The duration of interphase periods and the growing season as a whole largely depends on varietal characteristics and the type of fertilizer. At the same time, it should be noted that the use of mineral fertilizers leads to the extension of these indicators in all cultivated hybrids by an average of 1-10 days. And accordingly, the longest growing season in cultivated spring rape hybrids was noted in the 6th version of the experiment, where N45P45K45 + Fitomare (0.6 l/ha in the full seedling phase) + Fitomare (0.6 l/ha in the rosette phase) + Fitomare (0,6 l/ha budding phase), and the shortest, respectively, on the control variant without fertilizer application and on the 2nd variant of the experiment where N45P45K45 was applied. The highest indicators of plant height, the number of first-order branches on plants, the number of pods on plants, the weight of 1000 seeds and, accordingly, the level of seed yield in the years of research using different fertilizer options were obtained in the Delight hybrid. The lowest values of the above indicators in cultivated hybrids of spring rape were noted on the control version, and the use of mineral fertilizers leads to their growth. And accordingly, the best fertilizer options for Belinda, Mirko KL and Dilight hybrids are option 4, where N45P45K45 + N30 was applied (for top dressing in the budding phase) and option 6, where N45P45K45 + Fitomare was applied (0.6 l/ha in the full seedling phase) + Fitomare (0.6 l/ha in the rosette phase) + Fitomare (0.6 l/ha in the budding phase). Such characteristics as fat content and erucic acid content did not depend on the conditions of the growing season, but to a greater extent depended on the fertilizer option and the level of seed yield. At the same time, the highest content of fat in the seeds of the grown hybrids of spring rape was noted in the control variant, since there was the lowest yield, and accordingly, the use of increased doses of fertilizers leads to a decrease in the values of this indicator, and the lowest values in the cultivated varieties were obtained in the variants of the experiment 4 and 6, where the introduction was applied N45P45K45 + N30 (in top dressing in the budding phase) and N45P45K45 + Fitomare (0.6 l/ha in the full seedling phase) + Fitomare (0.6 l/ha in the rosette phase) + Fitomare (0.6 l/ha in the budding phase ) respectively. As for the content of erucic acids, the lowest values in hybrids were noted in the control options without the use of fertilizers, and the use of different doses of fertilizers leads to an increase in the values of this indicator, and the highest values were obtained in the fertilizer options 4 and 6, where N45P45K45 + N30 were applied, respectively (in top dressing in budding phase) and N45P45K45 + Fitomare (0.6 l/ha in the full seedling phase) + Fitomare (0.6 l/ha in the rosette phase) + Fitomare (0.6 l/ha in the budding phase).